2022
DOI: 10.1083/jcb.202206040
|View full text |Cite
|
Sign up to set email alerts
|

V. cholerae MakA is a cholesterol-binding pore-forming toxin that induces non-canonical autophagy

Abstract: Pore-forming toxins (PFTs) are important virulence factors produced by many pathogenic bacteria. Here, we show that the Vibrio cholerae toxin MakA is a novel cholesterol-binding PFT that induces non-canonical autophagy in a pH-dependent manner. MakA specifically binds to cholesterol on the membrane at pH < 7. Cholesterol-binding leads to oligomerization of MakA on the membrane and pore formation at pH 5.5. Unlike other cholesterol-dependent cytolysins (CDCs) which bind cholesterol through a conserved ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…For example, vacuolating cytotoxin (VacA) of Helicobacter pylori can cause dysfunctional autophagy leading to apoptosis (Yahiro et al, 2015). A newly identified cytotoxin MakA of Vibrio cholerae can induce non‐canonical autophagy and apoptotic death in the target nucleated cells (Jia et al, 2022; Nadeem et al, 2021). In another recent study, Vibrio cholerae cytolysin (VCC) has been shown to trigger pore formation‐independent apoptotic cell death in its target cells (Kaur et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…For example, vacuolating cytotoxin (VacA) of Helicobacter pylori can cause dysfunctional autophagy leading to apoptosis (Yahiro et al, 2015). A newly identified cytotoxin MakA of Vibrio cholerae can induce non‐canonical autophagy and apoptotic death in the target nucleated cells (Jia et al, 2022; Nadeem et al, 2021). In another recent study, Vibrio cholerae cytolysin (VCC) has been shown to trigger pore formation‐independent apoptotic cell death in its target cells (Kaur et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…CASM can be triggered by pathogen-encoded proton channels (Beale et al, 2014; Ulferts et al, 2021; Jia et al, 2022), proton-selective ionophore drugs (Jacquin et al, 2017; Fletcher et al, 2018), or the alkalisation of phagosomes (in a process termed LC3-Associated Phagocytosis, or LAP) (Sanjuan et al, 2007; Fletcher et al, 2018; Hooper et al, 2022). Recently, the innate immune signalling protein STING has also been shown to induce CASM via proton channel activity within the Golgi, reinforcing its connection to the neutralisation of acidic compartments (Fischer et al, 2020; Liu et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…A prevalent mechanism of non-canonical ATG8 conjugation involves V-ATPase that directly binds ATG16L1 and recruits the ATG12-ATG5-ATG16L1 conjugation complex to membranes 29,30 . Non-canonical ATG8 conjugation has been shown to occur in response to different stimuli and its physiological roles have been demonstrated [31][32][33][34] . Further identification of noncanonical ATG8 conjugation under various stimuli will enhance understanding of its functions and mechanisms.…”
Section: Introductionmentioning
confidence: 99%